Targeting type 2 inflammation in bullous pemphigoid: current and emerging therapeutic approaches - Toh, Wu Han; Lee, Hua-En; Chen, Chun-Bing (Frontiers in Medicine, 2023)
Bullous pemphigoid (BP) is one of the most common autoimmune bullous diseases and mainly affects an elderly population with multi-morbidity. Due to the frailty of many BP patients, existing treatment options are limited. The blisters associated with BP result from IgG and IgE autoantibodies binding to the central components of hemidesmosome, BP180, and BP230, stimulating a destructive inflammatory process. The known characteristic features of BP, such as intense pruritus, urticarial prodrome, peripheral eosinophilia, elevated IgE, as well as recent expanding evidence from in vitro and in vivo studies implicate type 2 inflammation as an important driver of BP pathogenesis. Type 2 inflammation is an inflammatory pathway involving a subset of CD4+ T cells that secrete IL-4, IL-5, and IL-13, IgE-secreting B cells, and granulocytes, such as eosinophils, mast cells, and basophils. It is believed that effectors in type 2 inflammation may serve as novel and effective treatment targets for BP. This review focuses on recent understandings of BP pathogenesis with a particular emphasis on the role of type 2 inflammation. We summarize current clinical evidence of using rituximab (B-cell depletion), omalizumab (anti-IgE antibody), and dupilumab (anti-IL-4/13 antibody) in the treatment of BP. The latest advances in emerging targeted therapeutic approaches for BP treatment are also discussed.